Core Outcome Sets for Pain Disorders: A Systematic Review of Research and Reporting Quality - Cui Y; Li B; Jiang S; Li Y; Wang S (Journal of Pain Research)
Ying Cui,1– 3,* Bo Li,1– 3,* Shiyi Jiang,4 Yuxian Li,1– 3 Sixuan Wang1– 3 1Department of Acupuncture, First Teaching Hospital of Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of China; 2Department of Acupuncture, National Clinical Research Center for Chinese Medicine Acupuncture and Moxibustion, Tianjin, People’s Republic of China; 3Department of Acupuncture, Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of China; 4Department of Rehabilitation, Wuxi Xishan District Hospital of Traditional Chinese Medicine, Wuxi, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bo Li, Department of Acupuncture and Moxibustion, First Teaching Hospital of Tianjin University of Traditional Chinese Medicine, No. 314, Anshan Xi Road, Nankai District, Tianjin, 300072, People’s Republic of China, Email ibou119@163.comPurpose: To systematically review the current research status of Core Outcome Sets (COS) for pain-related diseases and to evaluate the methodological quality of existing COS.Methods: Two researchers independently conducted a comprehensive search of both English and Chinese databases. Studies were screened and data were extracted based on predefined inclusion criteria. The methodological quality of the identified COS was assessed using the Core Outcome Set-STAndards for Development (COS-STAD), which includes 11 criteria covering the scope, stakeholder involvement, and the consensus process.Results: 24 COS were included in the final analysis out of 2150 records initially identified. These COS were primarily developed by organizations or research teams in Europe, Asia, and North America. The included COS covered 22 pain-related disorders, most of which (8 [33%]) were classified as symptoms, signs, or clinical findings according to the ICD-11 classification. One or more of the eight recognized methodologies were used in developing each COS. The most common combination included systematic reviews, Delphi surveys, qualitative interviews, and consensus meetings (6 [25%]). Among key stakeholder groups, clinical experts were most frequently involved (22 [92%]), whereas industry representatives were less engaged (5 [21%]). Only 5 COS (20%) fully met the 11 COS-STAD criteria, indicating room for methodological improvement. The highest scores were for health issue coverage (24/24 points), followed by the involvement of healthcare professionals in reflecting disease experiences (23/24 points). In contrast, the average score for intervention coverage was lowest (15/24), followed by constructing the initial outcome list (18/24). These findings suggest that greater emphasis should be placed on incorporating the perspectives of both professionals and patients during the initial outcome selection process.Conclusion: The development of Core Outcome Sets should adhere closely to guidelines established by the Core Outcome Measures in Effectiveness Trials (COMET) Initiative. Greater emphasis should be placed on the inclusion and evaluation of interventions. In addition, the perspectives of healthcare professionals and patients should be more thoroughly integrated during the design of the initial outcome list to enhance the relevance and applicability of COS in clinical practice.Keywords: pain, core outcome set, methodological quality assessment, systematic review